Korelasi Kualitas Tidur dan Kualitas Diet dengan Kadar Hemoglobin pada Remaja Putri: Correlation of Sleep Quality and Diet Quality with Hemoglobin Levels in Adolescent Girls - Pibriyanti, Kartika; Safitri, Desnika Irfadianis Intan; Damayanti, Amilia Yuni; Mufidah, Indahtul; Luthfiya, Lulu’; Arifah, Dian Afif (Amerta Nutrition, 2025)
Background: Iron deficiency is a common health issue among adolescent girls, mainly due to poor eating habits and inadequate sleep. The prevalence of anemia in this group remains high, ranging from 40% to 88%. Objectives: This study aimed to examine the relationship between nutritional intake, diet quality, and sleep quality with hemoglobin levels among adolescent girls. Methods: A cross-sectional study was conducted with 80 adolescent girls aged 15–19 years, selected from a population of approximately 230 adolescent girls in Ponorogo. Hemoglobin levels were measured using the Easy Touch GCHB instrument via capillary blood sampling. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Nutritional intake was evaluated using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and diet quality was measured with the Diet Quality Index (DQI). Multinomial logistic regression analyzed the relationships between nutritional intake, sleep quality, and hemoglobin levels. Results: The study found that 50% of participants had normal hemoglobin levels, 42.5% had mild anemia, and 7.5% had moderate anemia. The mean hemoglobin level was 13.8, the average diet quality score was 57.47, and the mean sleep quality score was 7.33. Poor nutritional intake increased the risk of mild anemia by 20.32 times (OR=20.320, 95%CI=3.12-41.55, p-value=0.004). Moderate sleep quality increased the risk of mild anemia by 22.93 times (OR=22.932, 95%CI=2.91-182.55, p-value=0.013). Conclusions: Interventions to improve nutritional intake and sleep quality are essential for adolescent girls, as these factors are strongly associated with iron deficiency in this group.